Psychophysiological models of psychosomatic disorders and a comprehensive method of their correction using the method of self-transcendental psychosomatic therapy - Сабадуха, Олексій (Psychosomatic Medicine and General Practice, 2023)
This text is the abstract of the poster presentation for the conference "Psychosomatic Medicine: SCIENCE AND PRACTICE"